Spatial Formats under the Global Condition - Middell, Matthias; Marung, Steffi (Dialectics of the Global, 2019)
Contributions to this volume summarize and discuss the theoretical foundations of the Collaborative Research Centre at Leipzig University which address the relationship between processes of (re-)spatialization on the one hand and the establishment and characteristics of spatial formats on the other hand. Under the global condition spatial formats are products of collective negotiations on the most effective and widely acceptable balance between the claim for sovereignty and the need for interconnectedness.